Age and Interleukin-15 Levels Are Independently Associated With Intima-Media Thickness in Obesity-Related NAFLD Patients - Tarantino, Giovanni; Citro, Vincenzo; Balsano, Clara; Capone, Domenico (Frontiers in Medicine, 2021)
Abstract Common carotid intima-media thickness (IMT) represents a functional and structural marker of early atherosclerosis. Macrophage cells, which have been detected in adipose tissue and atherosclerotic plaques are regulated by interleukin-15 (IL-15). We retrospectively evaluated in a population of 80 obese patients, median age 46 years (34-53) with low rate of co-morbidities but non-alcoholic fatty liver disease (NAFLD) or hepatic steatosis (HS) the relationship between IMT and serum concentrations of IL-15. Anthropometric measures, metabolic profile and serum inflammatory markers were analysed as well as well as levels of IL-15, MCP-1, b FGF and GM-CSF by a bead-based assay. IMT, HS and visceral adipose tissue were detected by ultrasonography. IL-15 levels of the obese were increased respect to those of 44 young healthy subjects, i.e., 2.77 (1.21-4.8) versus 1.55 (1-2.4) pg/mL, P= 0.002. At univariate analysis, IL-15 levels were associated to IMT and to those of MCP-1, b FGF and GM-CSF, without any relation to other inflammatory markers such as CRP and ferritin, except fibrinogen. At multivariate analysis, after adjusting the HS severity for the extent of visceral adiposity a dramatic change in prediction of IMT by HS was showed (β from 0.29 to 0.10, P from 0.008 to 0.37). When visceral fat was combined with Il-15 on the one hand, and the well-known CAD risk factors – i.e. age, gender, smoking status, HDL-cholesterol concentrations, triglycerides levels on the other, only age and IL-15 remained predictors of IMT (β= 0.60, P =.0001 and β= 0.25 , P= 0.024, respectively). There was neither association of IL-15 with various anthropometric parameters, nor with body fat distribution and severity of HS, also after adjusting for age. Age is resulted to be the main factor in the prediction of IMT and thus of early atherosclerosis. The prediction of IMT by IL-15 coupled with the lack of prediction by the well-know CAD risks is in agreement with recent data, which emphasise the main role of immune system in the onset/worsening of atherosclerosis, even though the role of visceral adiposity should be further deepened.